KERENTANAN TIGA JENIS ROTAN KOMERSIL TERHADAP SERANGAN JAMUR - Sihati Suprapti (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
The result of a study on the susceptibility of rattan to fungal attack. Three rattan species i.e. irit (Calamus trachy- coleus Becc.), manau (C. manan Miq.) and semambu (C. scipionum Lour.) both peeled and unpeeled were kept out door. Fungal infestation was than observed after one, two, four and eight week periods. At the end of experiment, each rattan sample was split into two halves to observe internal discoloration. The result showes that irit was most susceptible to stain attack and infestation on peeled cane seems to be more severe compared with unpeeled ones. The average rate of infes- tation of the rattan species studied was 10.59 % (4.65 - 14,92 %) per week. The lowest and highest rate of infestation were shown respectively by unpeeled manau and peeled irit rattan. It was also revealed that 93.33 % of the test speciments were internally stained, of which 46.67 % were badly stained. Semambu rattan seems to beresistant to fungal infestation, most of which showing low degree of internal stain.